Anticlastogenic activity of aqueous extract of Agaricus blazei in drug-metabolizing cells (HTCs) during cell cycle - Matuo, R.; Oliveira, R. J.; Silva, A.F.; Mantovani, M. S.; Ribeiro, L. R. (Taylor & Francis Inc, 2007)
The mushroom Agaricus blazei has been extensively investigated because of evidence of its antimutagenic, antitumor, and anticarcinogenic activities. This study investigated the clastogenic and/or anticlastogenic activity of aqueous extract of Agaricus blazei (10% w/v) in drug-metabolizing rat hepatoma tissue cells (HTCs), with continuous treatment and treatment during different phases of the cell cycle. DNA damage was induced utilizing two directacting agents-methyl methane sulfonate and ethyl methane sulfonate-and two indirect-acting agents-2-aminoanthracene and cyclophosphamide. The aqueous extract of A. blazei with either continuous treatment or treatment during different phases of the cell cycle showed clastogenic activity. The results with continuous treatment showed that A. blazei does not protect against DNA damage-inducing agents that are direct acting. Meanwhile, when combined with indirect-acting agents, a protective effect was demonstrated. A protective effect was also found during different phases of the cell cycle when cells were treated with indirect-acting agents. The protective effects against indirect-acting agents (continuous treatment and during the different phases of the cell cycle) suggest that A. blazei may provide some health benefits to the public when used as a functional food.
Keywords: Agaricus blazei; anticlastogenicity; HTC; direct and indirect-acting agents